Anxiety Disorders in Late Life: Considerations for Assessment and Cognitive-Behavioral Treatment. Issue 3 (August 2022) - Erickson, Julie; Rector, Neil A.
Highlights: Older adults with anxiety disorders do not have sufficient access to cognitive-behavioral treatment. Diagnosing anxiety disorders in late life requires consideration of how age-related factors can impact symptom presentation. Cognitive-behavioral treatment can and should be modified to meet the needs of older adults with anxiety disorders. There is a pressing need to increase research on, and dissemination of, cognitive-behavioral therapy protocols for older adults with anxiety disorders. Abstract: Anxiety disorders are among the most frequently diagnosed mental disorders in late life. As older adults comprise a growing segment of the population, evidence-based treatments for anxiety disorders in late life have come into sharper focus. Cognitive-behavioral therapy (CBT) for anxiety disorders in late life has received less empirical attention and widespread dissemination relative to other age groups. Increasing older adults' access to timely assessment and effective treatment can help reduce the personal and societal costs of anxiety disorders. The purpose of this review paper is to discuss important considerations for the assessment of anxiety disorders in older adults and offer adaptations to CBT treatment for this population. As part of assessment considerations, we discuss how physical health conditions, cognitive impairment, and functional limitations can impact anxiety disorder diagnoses with older adults. We also outline validated self-report measures of anxiety disorder symptoms for older adults and highlight the importance of assessing older adults' suitability for CBT. Several recommendations for adapting CBT protocols for older adults with anxiety disorders are described, such as extending psychoeducation, altered treatment pacing, use of content aids, and medical contraindications for interoceptive exposure. A case study is included that illustrates helpful assessment and treatment adaptions for an older woman with panic disorder. We highlight the pressing need to increase research and dissemination of CBT for anxiety disorders for older adults to meet the needs of an increasing segment of the population worldwide.